2019
DOI: 10.3390/ijerph16204000
|View full text |Cite
|
Sign up to set email alerts
|

Toileting Behaviors Related to Urination in Women: A Scoping Review

Abstract: This scoping review explores the state of science regarding women’s toileting behaviors, gaps in knowledge, and areas for future research. Online databases were searched to identify papers published in English between January 2010 through July 2019; the search identified 25 articles. The Toileting Behaviors–Women’s Elimination Behaviors scale has been published in four validated language versions and used in 17 of the 25 studies. The most frequent behaviors include concern about public toilet cleanliness, dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
14
0
2
Order By: Relevance
“…Our study found time constraints, and rules and regulations to be common limitations to restroom use at work. Prior studies have shown that "waiting too long to urinate" is associated with LUTS in women [19,20] and that women in occupations where restroom use is limited have a higher prevalence of LUTS compared to those with less restricted restroom access [5,19,21]. Increased education for employers and changes to the way time for restroom use affects interpretation of "productivity" by employers is necessary in order for women to be better able to manage bladder health in a work environment.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found time constraints, and rules and regulations to be common limitations to restroom use at work. Prior studies have shown that "waiting too long to urinate" is associated with LUTS in women [19,20] and that women in occupations where restroom use is limited have a higher prevalence of LUTS compared to those with less restricted restroom access [5,19,21]. Increased education for employers and changes to the way time for restroom use affects interpretation of "productivity" by employers is necessary in order for women to be better able to manage bladder health in a work environment.…”
Section: Discussionmentioning
confidence: 99%
“…Even the vandalism on public bathrooms shows gender differences [70]. These differences in scale scores may affect some of the reported problematic uses of bathrooms by women [32].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report that women's public bathroom interactions lead to adverse emotional outcomes [3,31]. Regarding the behavior related to public bathrooms, women try to limit the use of public bathrooms as a result of bad experiences with them that may result in bladder and other health problems [32]. Further, built environments tend to be less adjusted to women's needs in different areas [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Cabe salientar que a constipação intestinal crônica tem como consequências complicações clínicas severas como fecaloma, pseudodiarreia, volvo, além de ser um fator de risco para o desenvolvimento da incontinência urinária e baixa qualidade de vida (Assis et al, 2020;Schmidt et al, 2015;Wu et al, 2019).…”
Section: Orientações De Enfermagem Voltadas Para Prevenção De Agravos Intestinaisunclassified
“…Ainda nesse contexto, faz-se necessári9o destacar a incontinência urinária que é a perda de urina de caráter involuntário, condição em que muitos indivíduos convivem com esse problema acreditando ser normal e sentem-se constrangidos de comentar com familiares e amigos, ou ainda de buscar ajuda profissional. Contudo, existem repercussões econômicas, sociais, psicológicas e de saúde que este acometimento gera (Abrams et al, 2017;Wu et al,2019).…”
Section: Introductionunclassified